Potable water source and the method of garbage disposal in lowering the risk of diarrhea (Medical Journal of Indonesia, 2004)
The problem of diarrhea can be controlled through environmental factors and good habits. The Ministry of Health of the Republic of Indonesia has designed a simple indicator to evaluate the family health potential, the Family Health Potential Index (FHPI). This study aims to evaluate the effect of FHPI and other indicators on the risk of diarrhea. The data were obtained through a survey carried out by a team from the Family Physician Studies, Graduate Program of the Universitas Sebelas Maret. The survey was held from August to September 2003 in 5 provinces receiving the Family Health and Nutrition (FHN) project. The subjects were 1500 heads of poor families chosen by stratified random sampling. Interviews and observations were carried out by special trained interviewers and held in the subjectsâ homes. The use of potable water from the water system and well source built during the FHN project lowered the risk of diarrhea by 66% compared to the use of water from other sources (adjusted odds ratio= 0.34; 95% confidence interval = 0.16 - 0.70). Disposing of garbage using pits, sewers, rivers, or simply burying in the ground, increased the risk of diarrhea by twice compared with the specific method. Providing potable water from the water system or well and proving special tank for garbage disposal were important in order to lower the risk of occurrence diarrhea in a family. The use of non-dirt floors of houses as an FHPI specifically for diarrhea should be studied further. (Med J Indones 2004; 13: 119-26) Keywords: diarrhea, potable water, garbage disposal, family health potential index, poor family